2006
DOI: 10.1007/bf03262559
|View full text |Cite
|
Sign up to set email alerts
|

Caries in 4-year-old children after maternal chewing of gums containing combinations of xylitol, sorbitol, chlorhexidine and fluoride

Abstract: Less caries was observed in children of mothers who chewed gums with xylitol as the single sweetener during the time of eruption of the first primary teeth compared with those who used gums containing fluoride, sorbitol and lower amounts of xylitol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
40
1
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 16 publications
7
40
1
2
Order By: Relevance
“…9 The use of xylitol chewing gum reduced caries incidence from 30 to 65%, 8 in spite of its effectiveness still being discussed in literature. 10,13,14,15,16 Besides not being metabolized by oral bacteria, 7,17 leading to no pH drop in the biofilm, 18,19 xylitol penetrates into the bacterial cytoplasm and accumulates as xylitol 5-phosphate inside the cell. This impairs glycolysis and ATP production, and results in cell growth inhibition.…”
Section: Introductionmentioning
confidence: 99%
“…9 The use of xylitol chewing gum reduced caries incidence from 30 to 65%, 8 in spite of its effectiveness still being discussed in literature. 10,13,14,15,16 Besides not being metabolized by oral bacteria, 7,17 leading to no pH drop in the biofilm, 18,19 xylitol penetrates into the bacterial cytoplasm and accumulates as xylitol 5-phosphate inside the cell. This impairs glycolysis and ATP production, and results in cell growth inhibition.…”
Section: Introductionmentioning
confidence: 99%
“…According to Söderling [5], chewing gum with xylitol up to 3 times daily in pregnant females, and then new mothers, significantly reduces motherto-child SM transmission, though the relevance of sanation of the mother's oral cavity and preservation of appropriate dietary and hygienic instructions should not be neglected. Research by Thorild et al [2] has shown that administering chewing gum with xylitol (0.65 g of xylitol in 1 piece 3 times a day) by new mothers causes reduced caries occurrence, compared to using chewing gum with the addition of fluoride and sorbitol, but containing less xylitol. According to a meta-analysis of clinical trials with randomization regarding the reduction of the mother-to-child transmission of SM, chewing gum with xylitol causes a statistically-significant depletion of SM transmission, compared to using chewing gum with sorbitol or fluoride or chlorhexidine varnish [36].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to other sweeteners, it is not a substrate for the majority of bacteria existing in the oral cavity but a passive substitute for cariogenic sugars. It manifests anticarious action principally against Streptococcus mutans (SM) [2]. It inhibits the growth of SM in the presence of glucose, fructose, mannose, sorbitol and lactose, both in saliva and dental plaque, and decreases the amount of dental plaque [2][3][4][5][6].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A multifaceted intervention to reduce oral bacterial challenge in mothers was associated with both short-and longterm reductions in MS colonization (Köhler et al, 1984;Köhler and Andréen, 2012) and caries prevention in primary and permanent teeth Andréen, 1994, 2012). Interventions that provided mothers with xylitol-containing chewing gum successfully prevented child MS colonization and reduced child caries (Thorild et al, 2006;Söderling, 2009), although longer duration and higher dose regimens yielded greater effects (Söderling, 2009). Thus, early initiated and sustained interventions, perhaps integrating life course and socioenvironmental determinants perspectives (Kenney et al, 2012), might be best positioned for favorable outcomes.…”
Section: Discussionmentioning
confidence: 99%